2022
DOI: 10.1186/s13071-022-05380-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals dynamic expression of spleen lncRNAs and mRNAs in Beagle dogs infected by Toxocara canis

Abstract: Background Toxocara canis is a cosmopolitan parasite with a significant adverse impact on the health of humans and animals. The spleen is a major immune organ that plays essential roles in protecting the host against various infections. However, its role in T. canis infection has not received much attention. Methods We performed sequencing-based transcriptome profiling of long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression in the spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…It can be shown that dynamic balances between pro-inflammatory and anti-inflammatory responses, and immuno-suppressive and modulatory effects induced by T. canis infection, and the innate and adaptive immune response of the puppies against T. canis infection. These findings supported earlier findings that the dynamic balance between pro-inflammatory and anti-inflammatory responses mediates the growth of T. canis in the definitive canine host [ 11 , 12 ]. However, at 24 hpi, most of the DEmiRNAs regarding immune response were downregulated, suggesting that immune activity against T. canis infection may be attenuated in puppies at this stage of infection, whereas at 96 hpi when T. canis appeared in the lungs of puppies, and at 36 dpi when T. canis settles in the intestinal tract after completion of tracheal migration, the host’s immune response against T. canis infection and mild parasite suppression essentially reached a dynamic balance, especially at 36 dpi.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It can be shown that dynamic balances between pro-inflammatory and anti-inflammatory responses, and immuno-suppressive and modulatory effects induced by T. canis infection, and the innate and adaptive immune response of the puppies against T. canis infection. These findings supported earlier findings that the dynamic balance between pro-inflammatory and anti-inflammatory responses mediates the growth of T. canis in the definitive canine host [ 11 , 12 ]. However, at 24 hpi, most of the DEmiRNAs regarding immune response were downregulated, suggesting that immune activity against T. canis infection may be attenuated in puppies at this stage of infection, whereas at 96 hpi when T. canis appeared in the lungs of puppies, and at 36 dpi when T. canis settles in the intestinal tract after completion of tracheal migration, the host’s immune response against T. canis infection and mild parasite suppression essentially reached a dynamic balance, especially at 36 dpi.…”
Section: Discussionsupporting
confidence: 91%
“…Each group of Beagle puppies came from the same litter to reduce background differences, including three infected puppies and three control puppies. Procedures regarding infection, anesthesia, euthanasia, and spleen acquisition and storage were described in a previous study [ 11 ]. Briefly, Beagle puppies in the infected and control groups were orally infected with 300 embryonated T. canis eggs and equal amounts of saline, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent advances in understanding the molecular pathogenesis of T. canis infection in dogs has been facilitated by the application of high-throughput ‘omics’ approaches, including transcriptomics, proteomics and metabolomics [ 9 ]. For example, previous transcriptomic analysis allowed the identification of long noncoding RNA (lncRNA) and messenger RNA (mRNA) differentially expressed in the spleen [ 10 ] and lung [ 11 ] of Beagle dogs during T. canis infection. LncRNAs are cellular RNA transcripts with a length of > 200 nt [ 12 ] and regulate gene expression through a variety of mechanisms [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are increasing reports of the involvement of regulatory players in modulating the expression of genes at the transcriptional, posttranscriptional, translational and post-translation levels (Sudmant et al, 2015; Xu et al, 2022; Zhai et al, 2020) in different species and diseases state (Morenikeji et al, 2020; Tucker et al, 2021). Such regulatory players include long non-coding RNAs, micro RNAs and transcription factors (TF).…”
Section: Introductionmentioning
confidence: 99%